Creating a model of cross-task motivation — A meta-narrative review of the literature on dynamic motivation - Feyer, Frida K. (Frontiers in Psychology, 2023)
Substantial research on job motivation over the years has identified motivation to be essential to work outcomes such as well-being, attitudes, and performance. Yet, research on job motivation addressing temporal influences has been sparse. Existing research has addressed job motivation as an aggregation of the motivation for tasks, ignoring the possibility of temporal effects where the motivation for one task affects motivation in a subsequent task. The current meta-narrative review analyzes existing research on task motivation and synthesizes findings into a model of cross-task motivation. Using a predetermined search strategy, a systematic search yielded 1635 documents of which 17 were selected. Papers were analyzed using a meta-narrative approach. Four key meta-narratives were identified, contributing information from different research traditions. Synthesizing findings from these meta-narratives, a meta-theoretical model for understanding cross-task motivation was proposed. This model provides an extension of existing motivational theories elucidating temporal motivational processes. Implications for practitioners include the possibility of arranging jobs to maximize positive motivational outcomes.